PROSEDUR PENGUJIAN SUBSTANTIF AKUN PENDAPATAN PT ABC OLEH KANTOR AKUNTAN PUBLIK JEPTHA NASIB DAN JUNIHOL - Rizki Amaliyah, (2021)
Substantive tests are audit procedures designed in such a way as to detect material misstatements at the assertion level. Income is the inflow of economic activity in the form of income in the form of money that is oriented to earn a profit. Substantive testing is carried out based on the standards set in the audit program. The audit program itself is a program that has been created by the auditor to help the audit process to be more structured. The substantive testing carried out by the Public Accounting Firm Jeptha Nasib and Junihol began with planning an audit in the form of compiling an audit program and requesting data related to general company information and company financial information. Next, the income details are checked to check whether there are errors or not, then determine the amount of materiality to determine the sample. Next is the vouching process and compiling the Working Paper. After all substantive testing of the revenue accounts has been carried out, it can be concluded that the revenue accounts at PT ABC have been presented fairly and in accordance with applicable regulations.